PEMBELAJARAN BAMBOO DANCING SALAH SATU MODEL COOVERATIVE LEARNING UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS DI SEKOLAH DASAR - Zuraida Zuraida (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Thisss research is background overshadow by problems which during the time learn in study IPS still tend to to have the character of the ekspositoris and teacher sentris, less entangle the student in study, often give the items memorizing. Assessment which always the in form of cognate and less give the opportunity of at student to be got mixed up with to to solve problem [at] the study. For that researcher try to improve;repair the study IPS by using co-operative of learning of model bamboo dancing. this Research Type is research of class action ( Clasroom Action research), this research use the approach qualitative and kuntitatif doneby 2 is cycle by kolaboratif between researcher and class teacher. Result of this research indicate that the result learn the student mount from 66 at cycle I become 84 at cycle II. Compilation RPP mount from 71 at cycle I become 89 at cycle II. Activity Execution learn and student also mount from 65 and 69 at cycle I become 75 and 80 at cycle II. From research result doneinferential that by using co-operative of learning of model bamboo dancing can improve the result learn the student in study IPS in class of IV SDN 02Percontohn of Town Bukittinggi